Breaking Free of Control: How Conventional T Cells Overcome Regulatory T Cell Suppression - Mercadante, Emily R.; Lorenz, Ulrike M. (Frontiers in Immunology, 2016)
Conventional T (Tcon) cells are crucial in shaping the immune response, whether it is protection against a pathogen, a cytotoxic attack on tumor cells, or an unwanted response to self-antigens in the context of autoimmunity. In each of these immune settings, regulatory T cells (Tregs) can potentially exert control over the Tcon cell response, resulting in either suppression or activation of the Tcon cells. Under physiological conditions, Tcon cells are able to transiently overcome Treg-imposed restraints to mount a protective response against an infectious threat, achieving clonal expansion, differentiation, and effector function. However, evidence has accumulated in recent years to suggest that Tcon cell resistance to Treg-mediated suppression centrally contributes to the pathogenesis of autoimmune disease. Tipping the balance too far in the other direction, cancerous tumors utilize Tregs to establish an overly suppressive microenvironment, preventing anti-tumor Tcon cell responses. Given the wide-ranging clinical importance of the Tcon/Treg interaction, this review aims to provide a better understanding of what determines whether a Tcon cell is susceptible to Treg-mediated suppression and how perturbations to this finely-tuned balance play a role in pathological conditions. Here, we focus in detail on the complex array of factors that confer Tcon cells with resistance to Treg suppression, which we have divided into two categories: 1) extracellular factor-mediated signaling and 2) intracellular signaling molecules. Further, we explore the therapeutic implications of manipulating the phosphatidylinositol-3 kinase (PI3K)/Akt signaling pathway, which is proposed to be the convergence point of signaling pathways that mediate Tcon resistance to suppression. Finally, we address important unresolved questions on the timing and location of acquisition of resistance, and the stability of the “Treg-resistant” phenotype.